Effects of Various Hydroponic Systems in Increasing Caisim (Brassica Chinensis L.) Productivity Under LED Grow Light - Braja Manggala; Malinny Debra; Chatchawan Chaichana; Wahyu Nukholis Hadi Syahputra; Musthofa Lutfi (International Journal on Food, Agriculture and Natural Resources, 2023)
Hydroponics has been proven to increase crop production, particularly for leafy vegetable families, significantly. In addition, the hydroponic system can assist farmers in managing water and nutrition; as a result, this method is appropriate for sustainability as a real action to prevent further environmental damage caused by agricultural production. Several hydroponics systems have been invented; however, to get high plant yields, a selection of the system must be done by looking at the characteristics of the cultivated plants. Furthermore, artificial environmental conditions, such as light, temperature, and humidity, must be adjusted to accommodate the plant's requirements in a closed hydroponic system.  In this study, three hydroponics systems (i.e., wick technique, Nutrient Film Technique (NFT), and Deep Flow Technique (DFT)) were compared for morphology features, including the number of leaves, leaf width, plant height, wet root weight, and fresh weight. Caisim (Brassica chinensis L.) was grown on a single shelf; this design was intended to maximize land utilization in a closed area. Caisim's growing condition was under blue-red LED light for 35 days with a 16-hour illumination time at a distance of 15 and 20 cm. At harvest time, Caisim morphology utilizing the NFT approach produced a more significant (P < 0.05) result than the wick and DFT methods. Furthermore, on fresh weight, the LED at 15 cm outperformed the wick, DFT, and NFT at 20 cm by 20%, 47%, and 33%, respectively. According to the findings, the NFT approach combined with a 15 cm spacing distance or a light intensity of 250 PPFD was better and significantly impacted Caisim's shape.